Bleomycin in the setting of lung fibrosis induction: From biological mechanisms to counteractions. (July 2015) - Della Latta, Veronica; Cecchettini, A.; Del Ry, S.; Morales, M.A.
Graphical abstract: Abstract: Bleomycin (BLM) is a drug used to treat different types of neoplasms. BLM's most severe adverse effect is lung toxicity, which induces remodeling of lung architecture and loss of pulmonary function, rapidly leading to death. While its clinical role as an anticancer agent is limited, its use in experimental settings is widespread since BLM is one of the most widely used drugs for inducing lung fibrosis in animals, due to its ability to provoke a histologic lung pattern similar to that described in patients undergoing chemotherapy. This pattern is characterized by patchy parenchymal inflammation, epithelial cell injury with reactive hyperplasia, epithelial–mesenchymal transition, activation and differentiation of fibroblasts to myofibroblasts, basement membrane and alveolar epithelium injuries. Several studies have demonstrated that BLM damage is mediated by DNA strand scission producing single- or double-strand breaks that lead to increased production of free radicals. Up to now, the mechanisms involved in the development of pulmonary fibrosis have not been fully understood; several studies have analyzed various potential biological molecular factors, such as transforming growth factor beta 1, tumor necrosis factor alpha, components of the extracellular matrix, chaperones, interleukins and chemokines. The aim of this paper is to review the specific characteristics of BLM-induced lung fibrosis in different animal models and to summarize modalities and timing of in vivo drug administration. Understanding the mechanisms of BLM-induced lung fibrosis and of commonly used therapies for counteracting fibrosis provides an opportunity for translating potential molecular targets from animal models to the clinical arena.